Impact and Penetration of SiC: The Role of Rod Strength in the Transition from Dwell to Penetration. (2015) - Aydelotte, Brady; Schuster, Brian
Abstract: The phenomenon of dwell during projectile impact on ceramics has been an active area of research for several decades. Dwell in confined ceramics has received much attention, particularly the role of cover plates and their influence over the dwell to penetration transition. Dwell during long rod impact on unconfined ceramics has received relatively less attention. The present work will compare and contrast the results of two series of long rod impacts on hot pressed silicon carbide targets. One series utilized gold wire rods. The other series utilized rods fabricated from tungsten carbide with 10% cobalt matrix. A novel ten-flash X-ray system captured spatially resolved images of the penetration events. The experimental results are compared with simulations and predictions from the Alekseevskii-Tate equation to explore the role of shock pressure, the effects of the strength of the rod material in dwell to penetration transition behavior, and the behavior of defects within silicon carbide.